The twelve absolutes of leadership [ - Burnison, Gary , 1961- (McGraw-Hill, 2012)
For Gary Burnison, CEO of the world's largest executive search firm, these five simple words perfectly capture the essence of great leadership. There can be no half measures. Complete commitment, total engagement, and a powerful sense of personal responsibility are the criteria for true leadership excellence. It's more than a job; it's a way of life. But how do you get there? In this groundbreaking book, Burnison provides the answer. As the leader of Korn/Ferry International, Burnison is particularly well qualified to write a guide to effective leadership. On a personal level, he experiences every day what it's like to be responsible for the lives of others, the careers of his employees, and the expectations of stakeholders. He also deals one-on-one with some of the world's top leaders